PENGARUH KEPUASAN PELANGGAN PADA LOYALITAS PRODUK BERJEJARING - LESTARI, INTAN AFRILIA; KENCANA, I PUTU EKA NILA; SUKARSA, I KOMANG GDE (E-Jurnal Matematika, 2025)
Fulfilling needs through e-commerce services in modern day is in great demand. One of some popular e-commerce sites in Indonesia is Shopee. Noting there are many similar companies doing their businesses using digital media, Shopee needs efforts to be ahead of its competitors. This study aims to determine the causality of customer satisfaction using Shopee and its customer loyalty. The structural equation model (SEM) method, by using SPSS and SmartPLS 3.2 software, was used to answer the problem formulation. The data of this study were obtained directly from 100 respondents. The results of this study show that satisfaction has a significant effect on customer loyalty who purchases products on the Shopee network.